1995
DOI: 10.2331/fishsci.61.628
|View full text |Cite
|
Sign up to set email alerts
|

Algicidal Marine Bacteria Isolated from Northern Hiroshima Bay, Japan

Abstract: Marine bacteria that kill the noxious red tide flagellate Chattonella antiqua (Raphidophyceae) were screened and isolated from northern Hiroshima Bay, the Seto Inland Sea, Japan in 1991. Four strains (S, K, D, R) of Alteromonas spp. were selected and examined on characteristics of algicidal activities. Strains S and R showed wide algicidal range killing all cells of the 3 raphidophycean flagellates, 2 dia toms, and one dinoflagellate examined, in co-culture. Algicidal activities of the strains K and D depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 18 publications
0
95
0
Order By: Relevance
“…For example, Imai et al (1995), Nagasaki et al (1994a,b) and Tarutani et al (2000) reported that bacterial attack and viral infection induce bloom termination. To reveal the allelopathic interactions between phytoplankton species, we conducted bi-algal culture experiments using axenic cultures of S. costatum and H. akashiwo.…”
Section: Allelopathy Between Skeletonema Costatum and Heterosigma Akamentioning
confidence: 99%
“…For example, Imai et al (1995), Nagasaki et al (1994a,b) and Tarutani et al (2000) reported that bacterial attack and viral infection induce bloom termination. To reveal the allelopathic interactions between phytoplankton species, we conducted bi-algal culture experiments using axenic cultures of S. costatum and H. akashiwo.…”
Section: Allelopathy Between Skeletonema Costatum and Heterosigma Akamentioning
confidence: 99%
“…In the ERSEM model, for instance, it was formulated that lysis products from phytoplankton groups were partly particulate and partly dissolved, with the particulate fraction dependent on the actual nutrient cell quota (Baretta-Bekker et al, 1995, 1997. For primary producers, lysis was defined to included factors such as mechanical damage (e.g., sloppy feeding Imai et al, 1993;Strom et al, 1997), nutrient shortage (Berges and Falkowski, 1998), virus and bacteria activity (Imai et al, 1993(Imai et al, , 1995. A way to achieve this consisted in defining a background lysis rate, an increased lysis rate proportional to nutrient stress and a phytoplankton density dependent term.…”
Section: Current State Of Modelingmentioning
confidence: 99%
“…Chemical agents such as copper sulfate (Steidinger, 1983) and hydrogen peroxide (Ryu et al, 1998) have been performed as algicidal substances but are known to have a wide-spectrum in sterilizing effects. Viruses (Garry et al, 1998), bacteria (Imai et al, 1995), planktonic ciliates (Kamiyama, 2002) and heterotrophic dinoflagellates (Nakamura, 2002) as biological control also have been proposed. However, these methods also have the potential of disastrous environmental consequences (Jeong et al, 2000).…”
Section: Introductionmentioning
confidence: 99%